2014
DOI: 10.1111/ppl.12178
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nutrition alleviates the negative impacts of arsenic on the photosynthetic apparatus of rice leaves: an analysis of the key limitations of photosynthesis

Abstract: Silicon (Si) plays important roles in alleviating various abiotic stresses. In rice (Oryza sativa), arsenic (As) is believed to share the Si transport pathway for entry into roots, and Si has been demonstrated to decrease As concentrations. However, the physiological mechanisms through which Si might alleviate As toxicity in plants remain poorly elucidated. We combined detailed gas exchange measurements with chlorophyll fluorescence analysis to examine the effects of Si nutrition on photosynthetic performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 49 publications
2
36
0
5
Order By: Relevance
“…2008) and under Al, Cr and As toxicity in rice, mungbean, wheat and barley (Singh et al 2011;Ali et al 2013;Sanglard et al 2014;Tripathi et al 2015). These positive effects of Si are attributed to enhancement in gas exchange attributes and photosynthetic pigments under metal toxicity.…”
Section: Introductionmentioning
confidence: 87%
“…2008) and under Al, Cr and As toxicity in rice, mungbean, wheat and barley (Singh et al 2011;Ali et al 2013;Sanglard et al 2014;Tripathi et al 2015). These positive effects of Si are attributed to enhancement in gas exchange attributes and photosynthetic pigments under metal toxicity.…”
Section: Introductionmentioning
confidence: 87%
“…Application of Si significantly suppressed Zn accumulation in various plant parts, i.e., roots, and leaves of cotton, maize (Kaya et al, 2009;Anwaar et al, 2014;Bokor et al, 2014aBokor et al, , 2014b. In addition, it was shown that a significant negative correlation exist between external Si supply and arsenate and/or arsenite uptake and concentration in rice seedlings under hydroponic and soil culture conditions (Guo et al, 2005(Guo et al, , 2006(Guo et al, , 2007(Guo et al, , 2009Tripathi et al, 2013;Hu et al, 2013;Sanglard et al, 2014). Similarly, soil application of Si (silica gel, 10 g kg À 1 of soil) reduced the As concentration in straw, flag leaf, husk and grains of rice plants (Fleck et al, 2013).…”
Section: Decrease In Metal Uptake By Plantsmentioning
confidence: 95%
“…The interaction of Si with arsenic has received attention in recent years [42,47,[155][156][157] as it has a role in mitigating arsenic toxicity (Figure 1). A significant negative correlation was observed between Si concentration and uptake of inorganic arsenic species, and also for arsenic concentration in rice seedlings [136,158] because Si supply subdues the expression of the Si transporters Lsi1 and Lsi 2, the other mediators of arsenite uptake [2,42,143]. The application of Si in soil decreased the total arsenic accumulation in rice straw and grain by 78 and 16%, respectively [32,43]; strongly decreases the arsenic concentration in leaves and restricts the negative impacts on the photosynthetic apparatus [159].…”
Section: Role Of Silicamentioning
confidence: 97%